Caracterización geológica – geotécnica de la vía Taquil – Chantaco, kilómetro 0 – 2.0, ubicado en el cantón y provincia de Loja. - Cueva Guamán, Karina Stefany (2020)
This research document previous to obtaining the degree in Environmental Geology engineering and Territorial Planning, consists in the geological - geotechnical characterization of kilometer 0 - 2.0 of the Taquil - Chantaco road, located in the canton and Loja province, corresponding to a 2Km long, with a 200m study strip, which comprises an area of 40 Ha. The investigation begins with obtaining the topography in detail, which is obtained with the use of differential GPS with which was getting RTK terrestial control points and an UAV Mapper aerial vehicle unmanned; which allowed to generate an orthophoto in detail of the sector under study, as well as the generation of topography with contours every 1m. Based on the topography, the geological survey was carried out at a 1: 5000 scale, identifying outcrops and taking structural elements for the representation on the map; The predominant lithology in the sector is: porphidic andesitic tuffs, dacitic tuffs and tuff agglomerates. Once identified the main lithologies, it performed a geometric characterization RQD, RMR and GSI, in the most critical studies that are in the margin of the track, also were taken rock samples in these taludes, which were analyzed in the laboratory, determining mechanical physical properties of the rock matrix and the uniaxial compression. In the same way a geophysical exploration campaign was carried out in the 15 + 000 abscissa, the same that presented presentation the topographic conditions necessary to apply geophysics, for which were development 4 sev´s lines and 2 seismic lines; determining the subsoil layers in this sector. Finally, with the parameters getting in the tests, it was calculated the safety factor by using the software Slide 6.0. the same that determined the section of the road as stable.